2014
DOI: 10.1111/1440-1630.12148
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐site randomised controlled trial of evidence‐based supported employment for adults with severe and persistent mental illness

Abstract: The results support previous international findings that IPS-supported employment is more effective than non-integrated supported employment. IPS can be successfully implemented this way in Australia, but with a loss of effect strength compared to previous USA trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 32 publications
3
36
0
2
Order By: Relevance
“…Hoffmann et al and Howard et al and Heslin et al report the efficacy of IPS for the same patient population at two follow‐up periods, so we only included the latter study from both in our meta‐analysis. The meta‐analysis is based on 27 studies (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Hoffmann et al and Howard et al and Heslin et al report the efficacy of IPS for the same patient population at two follow‐up periods, so we only included the latter study from both in our meta‐analysis. The meta‐analysis is based on 27 studies (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Focused on principles of rapid job placement in positions matched to individual preferences with ongoing job support, the goal of this approach is competitive employment, defined as ‘community jobs that pay at least minimum wage(s)’ (Becker, Whitely, Bailey & Drake, ; p. 923). Originally developed in the USA, international evidence from multiple randomised controlled trials demonstrates that supported employment can significantly improve employment outcomes for people with severe mental illnesses, including in Australia (Bond et al ., ; Kinoshita, Furukawa, Kinoshita et al ., ; Waghorn et al ., ). Importantly, these trials show that barriers to employment can be overcome with the right support.…”
Section: Introductionmentioning
confidence: 97%
“…Accumulated evidence over twenty years has established the supported employment approach based on Individual Placement and Support (IPS) as a well‐defined, evidence‐based vocational intervention for people with severe mental illnesses (Bond, Drake & Becker, ; Kinoshita, et al ., ; Waghorn, Dias, Gladman, Harris & Saha, ). Focused on principles of rapid job placement in positions matched to individual preferences with ongoing job support, the goal of this approach is competitive employment, defined as ‘community jobs that pay at least minimum wage(s)’ (Becker, Whitely, Bailey & Drake, ; p. 923).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sector partnership IPS programmes in Australia have achieved variable outcomes in terms of employment placement rate. One programme achieved a 57% employment placement rate (Morris, Waghorn, Robson, Moore & Edwards, 2014), whereas others have been less successful, achieving between 28% and 43% employment placement rates (Waghorn, Dias, Gladman & Harris, 2015;Waghorn, Dias, Gladman, Harris & Saha, 2014;Williams, Lloyd, Waghorn & Machingura, 2015). Two of these studies reported on employment duration.…”
Section: Introductionmentioning
confidence: 99%